Use of Concrete Media to Improve the Understanding of Fraction Concepts of Grade III Students of SD Negeri Sirimomungkur - Sulaimah; Misman (Journal of Media and Learning Technology, 2025)
Mastering the concept of fractions presents a significant challenge for many third-grade students, often resulting in low conceptual understanding and difficulty in problem-solving. This study aimed to investigate the effectiveness of using concrete learning media to improve the comprehension of fraction concepts among students in Grade III at UPTD SPF SD Negeri Sirimomungkur. The research utilized a Classroom Action Research (CAR) design, structured into two cycles, with all third-grade students serving as participants. Data was collected through observation of teaching and learning activities and concept comprehension tests, including a pre-test and post-tests for each cycle. The findings indicate that the application of concrete media such as physical objects, shapes, and manipulatives significantly enhanced students' engagement and learning outcomes. The use of tangible resources made the abstract concept of fractions more accessible and relatable. There was a notable progression in student mastery. This approach successfully increased the percentage of students who achieved the Minimum Mastery Criteria (KKM) from the initial condition through Cycle I and Cycle II. This research concludes that concrete media is highly effective and recommended for teaching abstract mathematical concepts like fractions at the elementary level.